Advancing Direct Payment Reforms in Ontario and Scotland - Sarah Carbone; Sara Allin (McMaster University Library Press, 2020)
Over the last several decades, there has been an increased interest in cash-for-care programs internationally. Important among these reforms has been the emergence of direct payments (DPs), which are cash payments given directly to individuals so that they can purchase their own community care services. In the mid-1990s, both Ontario and Scotland implemented early direct payment programs with the explicit goals of providing greater choice and control over social services to adults with disabilities. Since then, however, the programs have diverged considerably. In Scotland, negative public perceptions resulted in DPs conversion into a program option embedded within the Self-Directed Support program. In Ontario, DPs have never been required by law and have instead expanded through multiple distinct programs funded through different government ministries. This paper compares the evolution of DPs in these two jurisdictions in order to better understand the actors and mechanisms that contributed to this divergence. Using the 3-I framework, we explore the ideas, interests and institutions that have shaped these reforms into their current structures. Our analysis offers several insights for other jurisdictions considering expanding direct payment reforms. These include recognizing: 1) policy conversion as a tool for managing negative perceptions of a reform, 2) policy levers for encouraging compliance among administering authorities, 3) divisions between health and social care as limiting possible expansion of the reform, and 4) program evaluations as justification for the reform's expansion.